Evaluation of Proso Millet (Panicummiliaceum L.) Germplasm for Yield and Related Traits in Godawari Municipality, Kailali, Nepal - Raut, Sanjay Kumar; Sharma, Rakshya; Ghimire, Ritambar; Rajbanshi, Devraj; Bohara, Binod (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
Proso millet (Panicummiliaceum L.), a short-duration C4 plant, is sparsely grown in mid hills of Karnali and Far western province during summer and rainy season. This crop has hugepotential for enhancing the food security in Nepal. To explore its suitability as a catch crop after wheat harvest in Terai, a field experiment was carried out considering 6 genotypes and 2 local varieties from Bajura, at Godawari municipality-8, Kailali. The experiment employed a randomized complete block design with 8 treatments and three replications. Data on plant height, panicle count/m2, panicle length, grain yield, straw yield, days to panicle emergence and maturity were analyzed and treatment means were compared at 5% level of significance. Results showed significant variation in growth, yield and yield attributes among the genotypes and varieties. Malchino exhibited smallest height, highest number of panicles/m2, smallest panicle, lightest seed, lowest grain sterility and short period to panicle emergence and maturity. Hence, Malchino yielded 3 times more grains and 2 times less straw than Dudhe chino, another popular variety from Bajura. Straw yield was significantly lower in Malchino, followed by NGRCO 7346, NGRCO7340, and Dudhe chino. NGRCO7339 produced significantly higher yield, revealing its potential to be grown as fodder crop in terai region. A significant positive association (r=0.96) between grain yield and harvest index, indicating that higher harvest index tend to produce higher yields, while an inverse correlation (r = -0.94) between grain sterility and grain yield suggested that lowering grain sterility could improve yield. The genetic analysis showed strong heritability and advancement for grain yield, highlighting its potential as a drought tolerant crop. The results also revealed that proso millet, a short cycle crop, is suitable for cultivation during the fallow period between two cropping season. The finding also suggests that further research needed to be conducted on date of planting to reduce grain sterility.